Effect of KnockOut serum replacement on germ cell development of immature testis tissue culture - Liu, Feng; Cai, Chunhong; Wu, Xin; Cheng, Yanxia; Lin, Tao; Wei, Guanghui; He, Dawei (Theriogenology, 2016)
To compare KnockOut serum replacement (KSR) and fetal bovine serum (FBS) for the development of germ cells. Testicular tissues from Sprague–Dawley rats were cultured for 4 weeks in culture media supplemented with FBS or KSR. Tissue area was measured at the beginning and end of the culturing period. Testicular histology, development of the germ cells, and the diameter of seminiferous tubules were analyzed by hematoxylin and eosin staining. After 4 weeks in culture, apoptosis and expression of the stage-specific spermatogenesis marker genes Kit, Sycp3, and Crisp1 were assayed. Tissues cultured in KSR-supplemented media were able to sustain growth and gradually increase seminiferous tubule diameter during the culture period. In addition, spermatogonia, primary spermatocytes, secondary spermatocytes, and round spermatids were observed after 4 weeks in culture, and reverse transcription-PCR confirmed expression of the marker genes. In comparison, tissues cultured in FBS-supplemented media showed dwindling testicular organization, necrotic seminiferous tubules, and expression of Kit, but inconsistent expression of Sycp3 and Crisp1 KnockOut serum replacement outperforms FBS as a growth media supplements for culturing immature spermatogonial tissue culture.